O leitor no tribunal subversivo de João Guimarães Rosa: a benfazeja à luz da teoria do efeito - Andrade, Fernanda de [UNESP]; Osorio, Ester Myriam Rojas [UNESP] (My University, 2013)
By understanding the reader as a central link to the meaning of the literary text and with the opportunity to extend the relevance of such studies, this work aims at analyzing the short story A benfazeja, by João Guimarães Rosa, with subsidies from Aesthetic Response Theory, by Wolfgang Iser. It investigates how structures of the text conduct the reading, in a subversive manner, by technique, repertory of themes, allusions, inversions of expectations, determinations and “gaps”. It verifies that there is an allegorical court with a persuasive rhetoric, in which the defense lawyer not only intends to protagonist MulaMarmela’s absolution, but also an invitation to new ways to see and judge to implied reader, beyond obvious reason and prejudice.

Ao compreender o leitor como elo fulcral à significação do texto literário e no ensejo de alargar a relevância de tais estudos, este trabalho tenciona analisar o conto A benfazeja, de João Guimarães Rosa, com os subsídios da Teoria do Efeito, de Wolfgang Iser. Investiga-se como as estruturas textuais conduzem um protocolo de leitura subversivo, por meio da técnica, do repertório de temas, das alusões, das inversões de expectativas, das determinações e dos “espaços vazios”. Verifica-se que há um tribunal alegórico com uma retórica persuasiva, no qual o narrador/defensor almeja não só a absolvição da protagonista Mula-Marmela, mas também um convite a novas formas de julgar para o leitor implícito, além da obviedade e do preconceito.
Keywords: Aesthetic Response Theory; Structures of the text; Guimarães Rosa; Teoria do efeito; Estruturas textuais; Guimarães Rosa